Pengembangan Media Gambar Pada Materi Setiap Manusia Berharga di Mata Allah Mata Pelajaran Pendidikan Agama Kristen dan Budi Pekerti Kelas IV Sekolah Dasar Kecamatan Sipoholon Tahun Pembelajaran 2024/2025 - Eunike Rehulina Ginting; Hasudungan Simatupang; Maria Widiastuti; Risden Anakampun; Senida Harefa (Sekolah Tinggi Pastoral Kateketik Santo Fransiskus Assisi, 2024)
The aim of this research is to produce image media which is motivated by the hopes of PAK teachers regarding the importance of image media in the material Every Human Being is Valuable in the Eyes of God in the learning of Christian Religious Education and Character in class IV Elementary School. The research uses a development approach (research and development) which aims to produce image media products that are effective for use in teaching Christian Religious Education and Character with the material that Every Human Being is Valuable in the Eyes of God for grade IV Elementary School.The research location is the State Elementary School in Sipoholon District, North Tapanuli Regency, consisting of Hutaraja Elementary School 174573, Pagar Batu Elementary School 178492 and Pagar Batu 177921. The research was carried out in May - August 2024. Development steps using the ADDIE model. From the research results it is known: 1) Analysis, results from interviews and questionnaires distributed to five teachers of Christian Religious Education and Character Education that 96.4% require the development of image media that makes it easier for teachers to teach, increases students' understanding, and can attract students' attention. on learning Every Human Being is Valuable in the Eyes of God. 2.) Design, A.) Making images of Every Human Being's Material is Valuable in the eyes of Allah. B.) Determination of Learning Materials: Every Human Being is Valuable in the Eyes of God from Genesis 1: 26a&31a, Psalm 139:13-16; Jeremiah 29:11; and John 3 : 16; Luke 3 : 11; Proverbs 17:17; Galatians 6 : 2; 1 Peter 2: 23). 3) Development, Validation results by linguists on the development of material image media. Every human being is valuable in the eyes of Allah, getting a score of 100% which is within the very valid criteria, or can be used without revision. The material expert's validation results achieved a score of 98% which is within the very valid criteria, or can be used without revision. The results of media validation reached a score of 74% after revisions/improvements reached a score of 100%, which is within the very valid criteria, or can be used without revision. Therefore, the images developed are valid for use in research trials. 4) Implementation, from the results of teacher responses in Sipoholon sub-district, the results were 91.3%, which was included in the very valid criteria or could be used without revision, according to responses from Christian Religious Education and Character Education teachers that the pictures were good. The response results for the small group trial obtained a result of 89%, and the large group trial obtained a result of 91.6%, which is within the very good criteria. It was concluded that the picture of Material Every Human Being is Valuable in the Eyes of Allah is Effective for use in learning. 5) Evaluation, seeing responses from experts, responses from PAK teachers, and students, image media is valid and suitable for use in the learning process because it can help teachers in learning and increase students' understanding and attract students' attention in learning.